Closure in Biblical Narrative - Zeelander, Susan (Leiden : BRILL, 2011)
Multiple and sometimes unexpected forms of closure in biblical narratives bring their stories to satisfactory close. Knowledge of these conventions and how they affect their stories is valuable to students of Bible and of narrative.
3.5.3. Stopping the Forward Momentum of a Narrative by 'Heaping Up'3.5.4. Revealing the Author's Didactic Interests; 3.5.5. Aesthetic Repetitions, Including Poetry, and Readers' Enjoyment; 3.6. Conclusion; Chapter Four Linguistic Devices; 4.1. Introduction; 4.2. Summaries: Recapitulation and Didactics; 4.2.1. Summaries in Epilogues; 4.2.2. Summaries from Diffferent Documentary Sources; 4.2.3. Single-Word Summaries; 4.3. Unqualified Assertions; 4.3.1. Absolute Words; 4.3.2. Hyperbole; 4.4. Tone of Authority; 4.5. Natural Stopping Points and Their Linguistic Motifs.
4.5.1. The Motif of Goal Completed.
Description based on print version record.
Keywords: Bible. O.T. Genesis -- Criticism, Narrative; Bible. O.T. Genesis; Biblical narrative; Closure (Rhetoric) in the Bible; Religion; Bible. -- Criticism, Narrative; Closure (Rhetoric) in the Bible; RELIGION / Biblical Studies / Old Testament; Electronic books